2006
DOI: 10.1002/jcc.20384
|View full text |Cite
|
Sign up to set email alerts
|

Epimerization and desaturation by carbapenem synthase (CarC). A hybrid DFT study

Abstract: The mechanism of the unusual epimerization and desaturation reactions catalyzed by carbapenem synthase was investigated using the hybrid density functional method B3LYP. Several different models have been used in the calculations to study five component reactions. Both protonated and deprotonated models for the substrate have been explored so that the effects of hydrogen bonds could be characterized. Besides the iron site, it is proposed that a some tyrosine residue, possibly Tyr67, is involved in the hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 25 publications
2
34
1
Order By: Relevance
“…Specifically, the reactive iron(IV)-oxo species abstracts H• of carbapenam 1 to give a C5-based radical, and subsequently a CarC active site tyrosine (Tyr67) functions as radical donor to donate a H• to the opposite face of the substrate radical to form 2, Fe III -OH and a tyrosyl radical. [27][28][29] Given the imperfection of the initially reported structure, the results of these studies appear to be suspectable. Recently, Chang et al reported a complete crystal structure of CarC in complex with substrate, iron(II), and 2OG with a resolution of 2.10 Å (PDB code: 4OJ8).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Specifically, the reactive iron(IV)-oxo species abstracts H• of carbapenam 1 to give a C5-based radical, and subsequently a CarC active site tyrosine (Tyr67) functions as radical donor to donate a H• to the opposite face of the substrate radical to form 2, Fe III -OH and a tyrosyl radical. [27][28][29] Given the imperfection of the initially reported structure, the results of these studies appear to be suspectable. Recently, Chang et al reported a complete crystal structure of CarC in complex with substrate, iron(II), and 2OG with a resolution of 2.10 Å (PDB code: 4OJ8).…”
mentioning
confidence: 82%
“…[28][29][30] However, there was no relevant discussion about the dioxygen binding site on metal and the formation of the Fe IV =O unit. A close inspection of the active site structure of CarC reveals that the 2OG binds to iron(II) in a bidentate manner and the sixth coordination site of iron(II) is occupied by a water ligand.…”
Section: Dioxygen Binding Site Previous Experimental and Theoreticalmentioning
confidence: 97%
“…This enzyme also catalyzes the preceding epimerization reaction as described in the following section. Some studies of CarC have considered the two reactions as being coupled (30,73), in which case a tyrosyl radical formed during the epimerization reaction could be used to generate a carbon-centered radical on the substrate. Alternatively, however, a ferryl intermediate could directly abstract a hydrogen atom of (3S,5R)-carbapenam in an uncoupled reaction.…”
Section: Desaturationmentioning
confidence: 99%
“…Epimerization, unusual among the Fe(II)/2OG oxygenases, is redox-neutral (75), and this unprecedented reactivity has led to intensive studies to investigate the mechanism. For example, the crystal structure of CarC in complex with the substrate analogue (S)-N-acetylproline along with analyses from computational studies led to several possible mechanisms for the epimerization of the C5 position involving a C5-radical intermediate and an external H-atom donor (30,73,76). Analysis of the initial crystal structure identified Tyr-67, located in a loop region near the active site and 5.7 Å away from the metal center, as a possible proteinbased H-atom donor (73).…”
Section: Epimerizationmentioning
confidence: 99%
See 1 more Smart Citation